Finite horizon model reduction and the appearance of dissipation in Hamiltonian systems - Barahona,M; Doherty,AC; Smaier,M; Mahuchi,H; Doyle,JC (2002)
An apparent paradox in classical statistical physics is the mechanism by which conservative, time-reversible microscopic dynamics, can give rise to seemingly dissipative behavior. In this paper we use system theoretic tools to show that dissipation can arise as an artifact of incomplete observations over a finite horizon. In addition, this approach allows us to obtain finite-time, low order, approximations of systems with moderate size, and to establish how the approach to the thermodynamic limit depends on the different physical parameters.